Pengawasan Internal Terhadap Disiplin Kerja Aparatur Sipil Negara Pada Dinas Sosial Kota Gunungsitoli - Eliagus Telaumbanua; Suka’aro Waruwu; Otanius Laia (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
− Internal control is a process carried out by the board of directors, management and other personnel within an entity, which is designed to provide adequate assurance regarding the achievement of objectives, with internal control creating a good atmosphere so that all duties and responsibilities can be carried out regularly with discipline. better work too.The formulation of the problem in this study is "Is there any influence of internal supervision on the work discipline of state civil servants at the Gunungsitoli City Social Service?".This study aims to determine the form of internal control that has been implemented and the form of work discipline that has been implemented and to find out how much influence internal control has on the work discipline of the State Civil Apparatus at the Social Service of Gunungsitoli City.The sample in this study was taken from the entire population of 23 people, due to the limited population. The method used in this research is a quantitative research method (Inferest), where the data collected is verified, validated, relied upon and tested the hypothesis using the t-test.Processing of data distribution t with dk = 21 and a significant level of 5% obtained ttable = 2,080. Thus, rcount> t table (4,617>2,080), with a correlation coefficient of 0,741.The results obtained by testing the coefficient of determination of 55% the effect of internal control on work discipline, while other factors not discussed in this study amounted to 45%.Based on the results of hypothesis testing, Ha is accepted and Ho is rejected, indicating that rcount > t table (4,617>2,080), so it can be said that there is an influence of internal control on the work discipline of the State Civil Apparatus.Keywords: Control, Internal, Discipline, Work